2018
DOI: 10.1002/cpt.1186
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Bias and Quality of Evidence for Treatment of ADHD With Stimulant Medication

Abstract: Storebø et al. provide a concise summary of two Cochrane reviews about benefits and harms of treatment of attention-deficit/hyperactivity disorder (ADHD) with methylphenidate: (1) a review of 185 randomized controlled trials that estimated benefits (e.g., moderate-to-large reduction in teacher-rated ADHD symptoms) and (2) a review of 260 nonrandomized trials that estimated harms (e.g., infrequent serious but frequent nonserious adverse events). They also mention (without providing much detail) additional infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…9 Even though methylphenidate has been used for over 60 years for this indication, the evidence concerning the benefits and harms of this medication in children, adolescents, and adults with ADHD remains uncertain. [10][11][12][13][14][15][16] Several studies have shown a possible favorable effect on ADHD symptoms, but the true magnitude of this effect is unknown. [10][11][12][13][14][15][16] In spite of these findings, a network meta-analysis from 2018 concluded that there is sufficient evidence to support short-term use within 12 weeks of methylphenidate in both children and adults, and there so far there are no trials investigating the effects beyond the 12-week treatment period or close to that.…”
Section: What Does the Evidence Show?mentioning
confidence: 99%
See 2 more Smart Citations
“…9 Even though methylphenidate has been used for over 60 years for this indication, the evidence concerning the benefits and harms of this medication in children, adolescents, and adults with ADHD remains uncertain. [10][11][12][13][14][15][16] Several studies have shown a possible favorable effect on ADHD symptoms, but the true magnitude of this effect is unknown. [10][11][12][13][14][15][16] In spite of these findings, a network meta-analysis from 2018 concluded that there is sufficient evidence to support short-term use within 12 weeks of methylphenidate in both children and adults, and there so far there are no trials investigating the effects beyond the 12-week treatment period or close to that.…”
Section: What Does the Evidence Show?mentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Several studies have shown a possible favorable effect on ADHD symptoms, but the true magnitude of this effect is unknown. [10][11][12][13][14][15][16] In spite of these findings, a network meta-analysis from 2018 concluded that there is sufficient evidence to support short-term use within 12 weeks of methylphenidate in both children and adults, and there so far there are no trials investigating the effects beyond the 12-week treatment period or close to that. 17 Some methodological problems with the network meta-analysis should be mentioned.…”
Section: What Does the Evidence Show?mentioning
confidence: 99%
See 1 more Smart Citation
“…Methylphenidate significantly increased adverse events considered non-serious and the risks of serious adverse events could not be assessed due to lack of data [7]. This review was heavily criticised in articles and editorials [8][9][10][11][12][13]. The criticism was focused on erratic inclusion of studies, risk of bias assessment, and assessment of the quality of included studies and meta-analyses as well as errors in the data.…”
Section: Introductionmentioning
confidence: 99%
“…challenge this notion, based on their ongoing work of Cochrane review, which critically examined existing evidence on the very issue of methylphenidate use in ADHD treatment. Their results provoked intense debate in the field, which is well described in the mini‐review by Swanson …”
mentioning
confidence: 99%